Pendidikan Dalam Pemikiran Ibnu Khuldun Dan Kh Ahmad Dahlan (Sebagai Refleksi Sistem Pendidikan Islam Indonesia Di Era Perkembangan) - Yunia Sari, Nia (Tarbawi: Journal of Islamic Education, 2020)
The era of modernization is an era where developments and changes cover all aspects of human life. The development of the times seemed to continue running and make a change that is so obvious. Every human who lives in this era seems to continue to experience spontaneous changes whether consciously or unconsciously. These developments and changes permeate all aspects of life, including those in the aspect of education. Education in the modern era continues to improve, educational actors are competing to improve the quality of education according to their development, following the times, following the wishes of the people who are currently very "literate" about the times. In this modern era, education is a very important thing to be mastered by every individual. The community is competing to get their children into schools that are considered qualified to get a decent education. Speaking of contemporary or modern education in Indonesia, is inseparable from the portrait of the thoughts of educational leaders who brought it into modern education as it is today. Indonesia's education formulation was formed based on educational thought by educational figures as the forerunner to the birth of education and continues to develop into the present. And it should be noted that in its development, the Indonesian education system is inseparable from history and one of them is about Indonesian education figures who should not be forgotten as a reflection of the Indonesian education system in this modern era.